Comprometimento organizacional na polícia civil do estado do Acre: um estudo de caso - Joao Evangelista Moreira Filho (2004)
The theme of this work is the Acre Civilian Police (PCAC) civil servantsorganizational engagement, after the advent of the Career, Employment and Salary Plan (PCCR). To this research a questionary was applied to 148 (one hundred and forty-eight) civil servants and three interviews were made with professionals directly involved with the elaboration and implement of PCCR, in order to check the improvement it might have brought. Organizational Engagement is the focus of the different approaches to the Administration thoughts aiming the relationship between the individual and the organization. The different views over that relation and the analysis of each approach is the basis and support to the development of studies on this theme. Acre Civilian Police have been searching, along with National Office of Public Security (SENASP), for offering more appropriate work conditions for their workers. Thisway, Security Unities were renovated and were given new equipment andworkers were trained in order to offer the best service to society. In addition, brand new computers were bought and the Security Unities were connected to the National System of Security Information (INFOSEG). Organizational Administration researches have been analyzing the problems of the relationship between organizations and workers, relating to the engagement. The reason for that is the essential function that human resources perform in the organizations, especially in the service rendering field. Success in an organization is directlyconnected to the workers quality of work and engagement. As most of theorganizations are technologically equalized, the competitive distinction has been made by the human resources of the institution. Thus, it is important to analyze and to diagnose the level of organizational engagement, as well as its possible determinants in that public institution. That engagement is connected to the individuals responsabilities and concern toward the function they performat work. The person has a complex and a multidimensional bond with his work and a variety of factors that interact with this dimension determine the personal level of organizational engagement. In order to identify this level of engagement at the PCAC, it was applied a questionary to 148 civil servants. As it can be seen on picture 02 at the data analysis, most of the civil servants from civilian police are men. Most of the professionals that were investigated studied until high school. 65,5% are men and 23,6% are women.6,1% from men and 2% from women studied till college. From the data analysis, based on factors like salary, career plan, work conditions, and according to the literature about the theme, it was possible to conclude that the organizational engagement of thosecivil servants is by and large ranked in low levels. In order to improve the level of engagement, it is necessary to make changes in PCCR for softening that problem. Taking into account quality and quantity, the strategy chosen had as its analysis population delegates, agents and police copyists from Acre Justice and Public Security Office.